Creative industries and the IPR dilemma between appropriation and creation: some insights from the videogame and music industries - Bach, Laurent; Cohendet, Patrick; Pénin, Julien; Simon, Laurent (Management international / Gestiòn Internacional / International Management, 2010)
Intellectual property rights (IPR) play a strategic role in creative industries. Defined as a collective process, creativity involves actors with contradictory IPR needs. This leads to an “IPR dilemna”. Firms are looking into appropriating creative work and prevent imitation; whereas creative communities need a weak IPR to combine past work and generate novelty. It becomes problematic for individuals to find themselves between these two. As a result, actors are developing specific IPR arrangements (e.g. open source and creative commons practices) to preserve the balance between appropriation and openness allowing creation. Two creative industries are used as illustrations: music and video-games.